Presence of Amphimachairodus coloradensis (Cook, 1922) (Felidae: Machairodontinae) in the Neogene of Hidalgo, Central Mexico - Ruiz Ramoni, Damián (2020)
The Neogene Amphimachairodus coloradensis appears to be one of the most abundant species of Machairodontine in Mexico. However, its fossil record is composed of scarce, fragmented, and poorly studied material. New remains discovered in La Plegaria locality (late Hemphillian), in the State of Hidalgo, in Central Mexico, offers the opportunity to review some morphological aspects and phylogenetic relationships of this species within the subfamily Machairodontinae. Our observations allow us to recognize that the material from La Plegaria looks like the paratype of A. coloradensis (DMNH EPV 207, from the Ogallala Fm. in the western United States); this means, m1 with reduced talonid and paraconid almost as large as protoconid, and p4 with posterior cingulum. Phylogenetic analysis confirms the relationship of La Plegaria felid with A. coloradensis and A. alvarezi; although the last one presents autapomorphies that differentiate it from others Amphimachairodus: highly developed mandibular flange. We concluded that the material from La Plegaria corresponds to the southernmost record of an A. coloradensis. This work made it possible to review variation within this species and its morphological relationship with M. catocopis.